2002
DOI: 10.2337/diabetes.51.7.2066
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of Skeletal Muscle Glycogen Synthesis and Glycolysis in Rosiglitazone-Treated Zucker Fatty Rats

Abstract: The aim of this study was to characterize insulin-stimulated skeletal muscle glucose metabolism in Zucker fatty rats and to provide insight into the therapeutic mechanism by which rosiglitazone increases insulinstimulated glucose disposal in these rats. Metabolic parameters were measured using combined in vivo 13 C nuclear magnetic resonance (NMR) spectroscopy to measure skeletal muscle glucose uptake and its distributed fluxes (glycogen synthesis and glycolysis), and 31 P NMR was used to measure simultaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…11,29,30 However, the present study as well as some recent reports show that even lower doses (3 to 5 mg/kg per day) of rosiglitazone for 7 to 14 days improve insulin sensitivity to the same extent. [31][32][33] In obese rats, fasting blood glucose levels were completely normalized to levels seen in lean rats, and plasma insulin values were reduced to similar extent with both treatment regimens of rosiglitazone.…”
Section: Discussionmentioning
confidence: 80%
“…11,29,30 However, the present study as well as some recent reports show that even lower doses (3 to 5 mg/kg per day) of rosiglitazone for 7 to 14 days improve insulin sensitivity to the same extent. [31][32][33] In obese rats, fasting blood glucose levels were completely normalized to levels seen in lean rats, and plasma insulin values were reduced to similar extent with both treatment regimens of rosiglitazone.…”
Section: Discussionmentioning
confidence: 80%
“…This increased plasma cholesterol was equally distributed among the three different lipoprotein fractions (i.e., VLDL, LDL, and HDL) (data not shown). These effects of Rgz are characteristic of the treatment of insulin resistance with PPAR ␥ agonists in rodent and human studies (2,3,(25)(26)(27).…”
Section: Characteristics Of Control and Rgz-treated Obese Zucker Ratsmentioning
confidence: 99%
“…Several studies with insulinresistant rodent models and type 2 diabetic patients have demonstrated that TZD treatment reduces both hyperinsulinemia and hyperlipidemia (1)(2)(3)(4)(5). Another important effect of TZDs is the normalization of insulin-stimulated whole-body glucose disposal, as reflected by an improved insulin action on skeletal muscle (2) and heart (4). TZDs are agonists of the peroxisome proliferator-activated receptor ␥ (PPAR ␥ ) (6,7).…”
mentioning
confidence: 99%
“…We obtain a total bolus of 0.423 g/kg. To transform expression 8 into volume values, we will consider an estimated glucose disposal rate (eGDR) of 33.2 mg/kg/min [36], duration of the bolus of 5 min, and a glucose solution of 200 g/L. The total volume can be calculated as shown in Eq.…”
Section: Total Glc Bolus G=kgmentioning
confidence: 99%